Blockchain-based Identity Management System: Desain dan studi Kemanan - Rahayu, Novi (CV. Generasi Insan Rafflesia, 2024)
The Internet of Things (IoT) is a number of devices that can collect and transmit data between sensors without the need for human assistance. However, the security of IoT can be threatened due to its nature that can be accessed from anywhere and at any time. Security gaps have the possibility of being difficult to detect, because they have a variety of patterns. Therefore, a secure model for sending data between sensors is needed. Blockchain is a technology that can answer the three necessary security requirements, namely availability, confidentiality, and integrity. In this research, we try to build an IoT security simulation using blockchain technology, where the security system uses the publicblockchain pattern. The method used in this research is a publicblockchain model that allows users to control applications connected to the emulator pin through smart contracts. This research uses the Ethereum network which is included in the testing network that can be used without any transaction fees that need to be paid. With this research, it is hoped that it can provide solutions to security problems and challenges faced in IoT networks.